12/15-lipoxygenase mediates disturbed flow-induced endothelial dysfunction and atherosclerosis - Jia Wei Chen; Shi Li Chen; Xin Rui Wu; Xin Yi Shu; Si Yi Tang; He Yuan; You Ran Li; Jin Wei Quan; Shuo Feng; Rui Yan Zhang; Chen Die Yang; Lin Lu; et al. (Molecular Medicine)
Abstract Background Disturbed flow regions in the vasculature are predisposed to endothelial dysfunction and atherosclerotic plaque formation. The enzyme 12/15-lipoxygenase (12/15-LOX, encoded by ALOX15) has emerged as a promising therapeutic target for atherosclerosis. However, the relationship between 12/15-LOX and disturbed flow-induced atherosclerosis remains uncharacterized. Methods Expression of 12/15-LOX in endothelial cells (ECs) exposed to steady flow and disturbed flow was compared in vivo and in vitro. The effect of 12/15-LOX on ECs was analyzed by using ALOX15 knockout mice, EC-specific adeno-associated virus (AAV)-mediated delivery of ALOX15-shRNA, and specific inhibitors. Partial carotid ligation mouse model was established to ascertain the role of 12/15-LOX in ECs under disturbed flow. Results Compared to steady flow regions, 12/15-LOX was significantly upregulated in ECs at disturbed flow sites. In vivo and in vitro experiments demonstrated that 12/15-LOX promoted disturbed flow-elicited endothelial dysfunction. Mass spectrometry analysis revealed that 12/15-LOX promoted production of 15 s-HETE, a pro-inflammatory eicosanoid metabolite, in ECs exposed to disturbed flow. Furthermore, we showed that disturbed flow activated 12/15-LOX expression through transactivation of its promoter by a mechanosensitive transcription factor sterol regulatory element binding protein 2 (SREBP2). Finally, EC-specific knockdown or inhibition of 12/15-LOX substantially attenuated the development of atherosclerosis in disturbed flow regions. Conclusions Disturbed flow promoted 12/15-LOX expression via SREBP2, thereby leading to increased pro-inflammatory PUFA metabolites and ECs dysfunction. Targeting at SREBP2-12/15-LOX pathway should provide therapeutic perspectives to attenuate disturbed flow-induced atherosclerosis. Graphical abstract